2008
DOI: 10.1371/journal.pgen.1000140
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Dosage Compensation in the Multiple X Chromosomes of the Platypus

Abstract: Dosage compensation has been thought to be a ubiquitous property of sex chromosomes that are represented differently in males and females. The expression of most X-borne genes is equalized between XX females and XY males in therian mammals (marsupials and “placentals”) by inactivating one X chromosome in female somatic cells. However, compensation seems not to be strictly required to equalize the expression of most Z-borne genes between ZZ male and ZW female birds. Whether dosage compensation operates in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 77 publications
7
74
0
Order By: Relevance
“…The percentage of cells with asynchronous replication was lower than that observed for the mouse X, suggesting partial DC. Consistent with this was RNA-in situ hybridization, which indicated that some X-specific genes were compensated by regulating the probability that they are either mono-or bi-allelically transcribed (Deakin et al, 2008). This is similar to the more recent observations in marsupials (Al Nadaf et al, 2010), although the sex chromosomes are not homologous.…”
Section: Marsupial XCIsupporting
confidence: 85%
“…The percentage of cells with asynchronous replication was lower than that observed for the mouse X, suggesting partial DC. Consistent with this was RNA-in situ hybridization, which indicated that some X-specific genes were compensated by regulating the probability that they are either mono-or bi-allelically transcribed (Deakin et al, 2008). This is similar to the more recent observations in marsupials (Al Nadaf et al, 2010), although the sex chromosomes are not homologous.…”
Section: Marsupial XCIsupporting
confidence: 85%
“…They have a complex sex chromosome system; for example, the platypus has ten sex chromosomes, females have five pairs of Xs and males have five Xs and five Ys (Grutzner et al 2004). A previous study demonstrated that while some genes on the platypus X are not dosage compensated, other genes show some form of compensation via stochastic transcriptional repression (Deakin et al 2008). Therefore, monotremes may not have a mechanism for dosage compensation that is comparable with that of eutherians and marsupials.…”
Section: Introductionmentioning
confidence: 99%
“…In the egg-laying monotremes, basal mammals that diverged from therians 166 Mya, multiple X chromosomes have homology not to the human X, but to the chicken Z chromosome (Veyrunes et al 2008). Like the chicken Z (Itoh et al 2007), platypus X chromosomes do not undergo inactivation, although some form of partial dosage compensation operates (Deakin et al 2008).…”
mentioning
confidence: 99%